A Phenomenological Studies of Special Education Teachers and Parents Lived Experiences In Upholding Learners With Disability (Lwd) In Transition Program During Pandemic (Faculty of Teacher Training and Education, Universitas Terbuka, 2022)
The implementation of a transition program for special education students is hardcore during face-to-face and it became more difficult to implement during distance education. The research aimed to explore the essence of the experiences of Special Education (SPED) teachers and parents under the transition curriculum. This study utilized qualitative design. Particularly, this study employed a phenomenological research design. The participants of this study were eight (8) parents having LWD at home enrolled in the school SY 2021-2022 under Special Education Program and five (5) SPED teachers. The information and replies of the participants were gathered using a semi-structured interview guide. Coding and triangulation were done to analyze and identify the emerging theme. The emerging themes for the teachers lived experiences revealed flexibility and adaptability in times of pandemic, the power of communication, and effective problem-solving strategies. For the parents, the main themes that emerged from their testimonies were the needs for assistance and parent as a manager. The findings also revealed that all problems related to the transition curriculum were addressed and solved by teachers and parents by working with each other. Knowing how parents struggles due to their work and parental roles helped the teachers to understand them and help them build a strong relationship based on trust and understanding. The researcher recommended that the school may intensify the relationship between the teachers and parents by improving communication, collaboration, and cooperation between them. To help the parents more in assisting their kids, parenting techniques, mentoring, and coaching programs may be provided.